Sentiment Collection and Analysis of Students in Classroom - Devansh Jain, A.Rajalakshmi, S.Ganesh Kumar (International Journal of Advanced Science and Technology, 2019)
The paper and the developed algorithm aims to enhance the quality of STEM Education given in Technical Colleges across India. The study combines researches done by several institutions (listed as references). The algorithm developed consist of five stages: Image Extraction, Image Recognition, Emotional Analysis, Data Warehousing, Data Analytics. The following results can be achieved by implementation of this algorithm: Understanding of particular student sentiment across a time period, favorability of a group of students towards a faculty, favorability of a class towards a subject.